Plurality in Muhammadiyah/Aisyiyah College and Fulfillment of Spiritual Well-Being for Non-Muslim Students: Pluralitas Di Perguruan Tinggi Muhammadiyah/Aisyiyah dan Pemenuhan Spiritual Well-Being Mahasiswa Non Muslim - Setiawan, Iwan (Universitas Muhammadiyah Sidoarjo, 2020)
Muhammadiyah / Aisyiyah College (PTMA) is a college that accepts students from various backgrounds, both Muslim and Non-Muslim (Catholic, Christian, Hindu and Buddhist). So it has an obligation to provide religious lessons for all students, both Muslims and Non-Muslims. In practice all students must take the Al-Islam and Kemuhammadiyahan (AIK) Courses. Non-Muslim students are also required to take AIK courses. Whereas Law Number 20 Year 2003 Article 12 Paragraph 1a explicitly states that education units have an obligation to provide religious subjects in accordance with the religion of the students. the same religion, In the implementation there are indeed problems in the practice of giving religious courses to non-Muslim students. Though students who have spiritual well-being or high spiritual well-being tend to have good spiritual. Giving religious subjects is one way to improve spiritual well-being.